Research on Sensorless Control of Permanent Magnet Synchronous Motor for Electric Vehicle - Jing Lian; Yafu Zhou; Jing Chang; Linhui Li; Xinhan Sun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Motor speed can’t change suddenly during the operation of motor because of inertia. In the short process of motor being not driven by motor controller, the operation of motor can be thought of as a uniform motion process. Making use of this property, it can be estimated next or next several cycles by measuring previous one or several cycles of motor. So the motor speed can be Figured out according to measured cycles. The phase angle can be estimated by zero crossing point of induced electromotive force produced in the running process of motor. Then the magnetic field position is estimated, and the angle measured by position sensors can be replaced by estimated angle. At last, bench test proves that this method can improve the reliability and safety of the motor control and has a good fault tolerance so as to be used as an auxiliary control method in motor control of electric vehicle and realize multi-mode control. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4005